1997
DOI: 10.1128/iai.65.11.4539-4547.1997
|View full text |Cite
|
Sign up to set email alerts
|

Response of Chlamydia trachomatis serovar E to iron restriction in vitro and evidence for iron-regulated chlamydial proteins

Abstract: Iron is a well-established mediator of virulence in several bacterial pathogens, yet little is known about the role of iron in infectious disease processes caused by obligate intracellular bacterial pathogens. In this study, the effect of iron limitation was examined for the sexually transmitted infectious agent Chlamydia trachomatis in an in vitro model of human genital infection using the intracellular iron-chelating reagent deferoxamine mesylate (Desferal). Iron restriction caused a significant reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 54 publications
3
89
0
Order By: Relevance
“…Undoubtedly, the ability to acquire iron would be crucial to the survival of chlamydiae, particularly C. trachomatis serovars D±K, which infect the genital mucosae and are subjected to fluctuating levels and sources of iron throughout the female menstrual cycle. A previous study in this laboratory confirmed that these organisms do respond to iron availability; EBs purified from genital epithelial host cells under iron-limiting growth conditions are significantly less infectious than those obtained from host cells growing in an iron-sufficient medium (Raulston, 1997). In addition, the synthesis of at least 20 chlamydial proteins is altered by the availability of iron.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Undoubtedly, the ability to acquire iron would be crucial to the survival of chlamydiae, particularly C. trachomatis serovars D±K, which infect the genital mucosae and are subjected to fluctuating levels and sources of iron throughout the female menstrual cycle. A previous study in this laboratory confirmed that these organisms do respond to iron availability; EBs purified from genital epithelial host cells under iron-limiting growth conditions are significantly less infectious than those obtained from host cells growing in an iron-sufficient medium (Raulston, 1997). In addition, the synthesis of at least 20 chlamydial proteins is altered by the availability of iron.…”
Section: Introductionmentioning
confidence: 59%
“…The chlamydiae are, however, subjected to certain environmental challenges within the host cell, not least of which is the competition for available iron. Studies in this laboratory have demonstrated the severe consequences of iron limitation upon chlamydial viability that is accompanied by enhanced synthesis of several chlamydial proteins (Raulston, 1997). These observations formed the basis for a careful analysis of each predicted ORF in C. trachomatis for distant relationships to Fur proteins; Fur is well-known for derepression resulting in increased synthesis of bacterial iron transport systems and virulence factors when bacteria are challenged with iron limitation.…”
Section: Discussionmentioning
confidence: 96%
“…The authors were unable to detect the protein in purified EB and, therefore, proposed that it is perhaps a protein specific for chlamydial RB. Likewise, only a trace amount of YtgA could be detected in EB purified from host cells using standard laboratory growth conditions, but YtgA was quantitatively increased by fourfold in EB purified from host cells propagated under iron-limiting growth conditions (Raulston, 1997). This observation may indicate that YtgA, as a predicted periplasmic metal-binding protein, is involved in iron acquisition by the chlamydiae.…”
Section: Discussionmentioning
confidence: 93%
“…The authors' laboratory efforts focus on the response of C. trachomatis genital isolates to iron deprivation using an in vitro polarized human endometrial epithelial cell model system (Raulston, 1997;Wyllie & Raulston, 2001). These studies are particularly relevant if one considers that iron sources in the endometrium fluctuate during menstruation (Zhu et al, 1995;Kelver et al, 1996;Andrews, 2000) and the majority of chlamydial infections are observed in individuals 15-25 years of age (Schachter & Grayston, 1998) representing peak fertility years.…”
Section: Introductionmentioning
confidence: 99%
“…122 IFN-g is involved in many processes that limit iron and other essential biometals to 123 intracellular pathogens as a component of host nutritional immunity (Cassat & Skaar,124 2013; Hood & Skaar, 2012). Chlamydia have a strict iron dependence for normal 125 development, evidenced by the onset of persistence following prolonged iron limitation 126 (Raulston, 1997). Importantly, Chlamydia presumably acquire iron via vesicular 127 interactions between the chlamydial inclusion and slow-recycling transferrin (Tf)-128 containing endosomes (Ouellette & Carabeo, 2010).…”
mentioning
confidence: 99%